118k views
4 votes
Use the Remainder Theorem to find the remainder for (2x^3-3x^2+6)/(x-1) and state whether or not the binomial is a factor of the polynomial.

User Evyan
by
4.6k points

2 Answers

5 votes

Answer:

Remainder= 0 and it is a polynomial

Explanation:

Got a 100% on edge 2020

User Cstrutton
by
5.3k points
3 votes

Answer:

Remainder= 5, and the binomial
(x-1) is not a factor of the given polynomial.

Explanation:

Given polynomial is
(2x^3-3x^2+6) , we have to divide this with a binomial [tex}(x-1)[/tex] using remainder theorem.

Remainder theorem says if
(x-a) is a factor then remiander would be
f(a)

Therefore for
(x-1), \ {we find}\  f(1)}


f(1)=(2* 1^3-3*1^2+6)\\1^3 =1\\1^2=1\\Substituting \ this \ above\\f(1)= (2-3+6)=5

Thus the remainder is 5 and since it is not 0 , so the binomial
(x-1) is not a factor of the given polynomial.

User Shachar Shemesh
by
5.2k points